Long-term survival outcomes of patients with Niemann-Pick disease type C receiving miglustat treatment: A large retrospective observational study - Patterson, Marc C; Garver, William S; Giugliani, Robert; Imrie, Jackie; Jahnova, Helena; Meaney, F John; Nadjar, Yann; Vanier, Marie T; Moneuse, Patrick; Morand, Olivier; Rosenberg, Daniel; Schwierin, Barbara; et al. (Journal of inherited metabolic disease, 2020)
Miglustat has been indicated for the treatment of Niemann-Pick disease type C (NP-C) since 2009. The aim of this observational study was to assess the effect of miglustat on long-term survival of patients with NP-C. Data for 789 patients from five large national cohorts and from the NPC Registry were collected and combined. Miglustat-treated and untreated patients overall and within sub-groups according to age-at-neurological-onset, that is, early infantile-onset (<2 years), late infantile-onset (2 to <6 years), juvenile-onset (6 to <15 years), and adolescent/adult-onset (≥15 years) were analysed and compared. Survival was analysed from the time of first neurological manifestation (Neurological onset group, comprising 669 patients) and from diagnosis (Diagnosis group, comprising 590 patients) using a Cox proportional hazard model adjusted for various covariates. Overall, 384 (57.4%) patients in the Neurological onset group and 329 (55.8%) in the Diagnosis group were treated with miglustat. Miglustat treatment was associated with a significant reduction in risk of mortality in both groups (entire Neurological onset group, Hazard ratio [HR] = 0.51; entire Diagnosis group, HR = 0.44; both P < .001). The effect was observed consistently in all age-at-neurological-onset sub-groups (HRs = 0.3 to 0.7) and was statistically significant for late infantile-onset patients in both groups (Neurological onset group, HR = 0.36, P < .05; Diagnosis group, HR = 0.32, P < .01), and juvenile-onset patients in the Diagnosis group only (HR = 0.30, P < .05). Despite the limitations of the data that urge cautious interpretation, the findings are consistent with a beneficial effect of miglustat on survival in patients with NP-C.
Keywords: výsledek terapie; 1-Deoxynojirimycin; Young Adult; analýza přežití; NP-C; survival; Male; NPC registry; retrospektivní studie; Child, Preschool; mladý dospělý; Internationality; Adolescent; 1-deoxynojirimycin; Infant; Niemannova-Pickova nemoc typu C; Child; dítě; Adult; internacionalita; Aged; dospělí; mužské pohlaví; senioři; Enzyme Inhibitors; Niemann-Pick Disease, Type C; registrace; Niemann-pick disease type C; Survival Analysis; mladiství; Treatment Outcome; novorozenec; předškolní dítě; senioři nad 80 let; lidé; ženské pohlaví; Humans; miglustat; Infant, Newborn; kojenec; Aged, 80 and over; Registries; Zavesca; Retrospective Studies; observational national cohorts; Female; lidé středního věku; inhibitory enzymů; Middle Aged